Mean-variance asset–liability management with partial information and uncertain time horizon. (3rd July 2021) - Peng, Xingchun; Chen, Fenge
ABSTRACT: This paper studies a mean-variance asset–liability management (ALM) problem with uncertain time horizon and partial information. The ALM can invest in an incomplete financial market consisting of one riskless asset and n risky stocks. The stocks price process is described by a multidimensional diffusion process with random coefficients. The uncontrollable liability process is modelled by a general diffusion process with hedgeable risks and unhedgeable risks. The uncertainty of the time horizon is assumed to come from randomness of financial assets and the liability and some other stochastic factors. The ALM may get only partial information about the liability. We derive efficient strategies and efficient frontiers in terms of the solutions of two BSDEs under complete and partial information. The closed-form expressions of efficient strategies and efficient frontiers are obtained under some special cases.